2023
DOI: 10.3390/ijms24032769
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the Gut Microbiome and Microbial-Derived Metabolites in Immune-Related Adverse Events: Emergence of Novel Biomarkers for Cancer Immunotherapy

Abstract: Immune checkpoint inhibitors (ICIs) have changed how we think about tumor management. Combinations of anti-programmed death ligand-1 (PD-L1) immunotherapy have become the standard of care in many advanced-stage cancers, including as a first-line therapy. Aside from improved anti-tumor immunity, the mechanism of action of immune checkpoint inhibitors (ICIs) exposes a new toxicity profile known as immune-related adverse effects (irAEs). This novel toxicity can damage any organ, but the skin, digestive and endocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 243 publications
1
12
0
Order By: Relevance
“…As previously mentioned, the role of the gut microbiome is vital in maintaining homeostasis in the host's gut and other sites, significantly influencing the development of irAEs 145,154 . Consequently, the role of specific gut microbiomes is gaining increasing recognition 139,143,149 . Future research should focus on identifying specific microbiomes that can optimise the outcomes of cancer immunotherapy.…”
Section: Mechanisms Of Ici‐induced Iraes In Nsclcmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously mentioned, the role of the gut microbiome is vital in maintaining homeostasis in the host's gut and other sites, significantly influencing the development of irAEs 145,154 . Consequently, the role of specific gut microbiomes is gaining increasing recognition 139,143,149 . Future research should focus on identifying specific microbiomes that can optimise the outcomes of cancer immunotherapy.…”
Section: Mechanisms Of Ici‐induced Iraes In Nsclcmentioning
confidence: 99%
“…Short‐chain fatty acids (SCFAs), including propionate, butyrate, acetate and valeric acid, are essential in engaging with immune cells, particularly colonic macrophages, and suppressing the synthesis of proinflammatory cytokines such as IL‐1, TNF‐α and IL‐6 144–146 . Similar to SCFAs, compounds such as indole‐3‐carboxaldehyde and polyamines, including spermine, are expected to offer defense against the development of irAEs 143,147 . Particularly, a study of the stool microbiota in 26 patients showed that most baseline phylotypes in those with colitis belonged to the Firmicutes group, whereas individuals without colitis fell under the Bacteroidetes category 148 .…”
Section: Mechanisms Of Ici‐induced Iraes In Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain bacteria have been identified to facilitate ICI responses and reduce ICI toxicities, including Akkermansia, Bifidobacterium, etc. 119 Chaput et al 25 showed that patients treated with ipilimumab with increased representation of Faecalibacterium and Firmicutes had increased efficacy of ICIs, as well as increased risk of developing colitis or other ICI-induced toxicities, which is known as the efficacy-toxicity coupling effect.…”
Section: Modulation Of Gut Microbiota Affects Iraes Of Immune Checkpo...mentioning
confidence: 99%
“…It is known that the microbiome plays an important role in human health and disease by modulating a host's innate and adaptive immune system, immune responses, and metabolism, and by protecting from invading pathogens [235][236][237]. The tumor microenvironment (TME) influences cancer progression and therapy responses [238] and many recent studies have demonstrated associations between the TME and microbiota composition and responses to immune checkpoint inhibitors in cancer patients, including NSCLC patients, suggesting that modulation of the microbiota through diet, probiotics, and fecal microbiota transplantations (FMT) could improve treatment efficacy [238][239][240][241][242][243][244]. There is also a possibility that the lung microbiome change could be used as a biomarker for detecting clinical phenotypes [245].…”
Section: Microbiomementioning
confidence: 99%